Budget Consolidation in a Difficult Environment - Ten Guidelines Plus a Preliminary Reality Check - Karl Aiginger; Margit Schratzenstaller (Austrian Institute of Economic Research (WIFO), 2010)
There is evidence that a budget consolidation strategy can work with only a small and short lived negative impact on growth. However, this time consolidation is taking place in the aftermath of a deep crisis which had lead to increased levels of uncertainty. In addition the financial sector, as well as its regulation is under reconstruction. Firms and consumers are deleveraging, and many countries are trying to consolidate at the same time. We develop ten guidelines for consolidation during such a difficult economic period. We compare them to other guidelines published and, to the extent possible, cross-check whether the upcoming consolidation programs being implemented or revealed in various countries comply with our guidelines. We propose to follow a "high road" on cutting deficits, which includes an active growth enhancing component during the consolidation period. The "active component" should be financed by deeper cuts in subsidies, by eliminating obsolete government expenditure as well as by increasing the efficiency of the public sector. Taxes should not be raised permanently - a temporary contribution to consolidation will be needed, but tax structures in general should be made more growth and employment friendly.
Keywords: 330; budget consolidation; financial crisis; tax and expenditure structure; Haushaltskonsolidierung; Wachstumspolitik; Nachhaltige Entwicklung; Wirkungsanalyse; EU-Staaten